2017
DOI: 10.12688/f1000research.12268.1
|View full text |Cite
|
Sign up to set email alerts
|

Professional medical writing support and the reporting quality of randomized controlled trial abstracts among high-impact general medical journals

Abstract: In articles reporting randomized controlled trials, professional Background medical writing support is associated with increased adherence to Consolidated Standards of Reporting Trials (CONSORT). We set out to determine whether professional medical writing support was also associated with improved adherence to CONSORT for Abstracts.: Using data from a previously published cross-sectional study of 463 Methods articles reporting randomized controlled trials published between 2011 and 2014 in five top medical jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As far as we are aware, the topic of this review has not been reviewed in other medical areas by pairing full-text manuscripts and abstract-only reports. However, there have been other studies and reviews which have assessed the use of abstracts and abstract-only reports and their adherence to reporting standards and peer review, and have found them suboptimal5–9 17–20 A recent review on trustworthiness assessment for SRs found that 25% or RCTs included in 18 Cochrane SRs should not have been included in the reviews, due to issues around research governance, study feasibility and the plausibility of the results and reported baseline characteristics 21. The authors propose a formal trustworthiness assessment as part of the screening process and an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we are aware, the topic of this review has not been reviewed in other medical areas by pairing full-text manuscripts and abstract-only reports. However, there have been other studies and reviews which have assessed the use of abstracts and abstract-only reports and their adherence to reporting standards and peer review, and have found them suboptimal5–9 17–20 A recent review on trustworthiness assessment for SRs found that 25% or RCTs included in 18 Cochrane SRs should not have been included in the reviews, due to issues around research governance, study feasibility and the plausibility of the results and reported baseline characteristics 21. The authors propose a formal trustworthiness assessment as part of the screening process and an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in other medical fields that abstract-only reports have both methodological and outcome data reporting flaws compared with full-text manuscripts. Abstract-only reports have been found to report data that are inconsistent with or absent from the full-text manuscript’s body, even in large-circulation general medical journals 5–7. Abstract-only reports can be at risk of substandard peer review,8 9 which could mean abstract outcome data used in evidence synthesis could be inaccurate.…”
Section: Introductionmentioning
confidence: 99%
“…The high level of acceptance of medical writing services of our respondents would allude to the benefits our cohort obtained from PMWS for a written manuscript. However, it is worth pointing out that there is a study that suggested that the use of professional writers did not improve the impact of the published article in terms of annual citations, article views, and altimetric score and did not show any increased adherence to CONSORT-A [ 33 , 34 ]. However, it must be noted that 12.3% of our respondents deemed it unethical to use PMWS.…”
Section: Discussionmentioning
confidence: 99%
“…Dataset used per Hays et al 9 with the addition of column C for this post hoc analysis by professional medical writing support (yes: 1; no: 0). doi, 10.5256/f1000research.12268.d172437 23 …”
Section: Data Availabilitymentioning
confidence: 99%